Território, fronteira, campesinato: expansão da fronteira agrícola e resistência camponesa no norte do Tocantins, Brasil - Reinaldo, Thayssllorranny Batista (2023)
The expansion of the agricultural frontier in the Legal Amazon region played a significant role in the creation of the State of Tocantins in 1988, both directly and indirectly. This expansion was driven by a fundamental political strategy aimed at integrating landowners and capitalist entrepreneurs into agricultural and technological modernization, primarily through agribusiness. The objective was to enrich companies involved in the production of grains and pulp for the global market in the 21st century. During this process, the Neoliberal State actively supported and encouraged policies that promoted agricultural expansion on traditionally lands inhabited by peasants. Consequently, social conflicts emerged between the regional peasantry (including squatters, riverside dwellers, settlers, babassu coconut breakers, traditional communities, and indigenous peoples) and the powerful forces driving agribusiness. These conflicts revolved around issues of land access, dignity, and improved living conditions, as the peasants struggled against oppression and expropriation resulting from the expansion of agribusiness into the countryside. These struggles directly impacted the human frontier, where the boundaries of agricultural development clashed with the rights and livelihoods of local communities (MARTINS, 2009). The northern region of Tocantins, functioning as a capitalist agricultural frontier, served as a territory for commodity production, generating income, and capital accumulation. Simultaneously, it represented a space of struggle, life, and hope for the peasantry. It was a place of abundance and affection, where the peasantry fought against the encroachment of agribusiness and its associated interests. The primary objective of the thesis was to analyze the reproduction of capital in the northern region of Tocantins through the study of the agricultural frontier as a space of conflict and peasant resistance. The research employed a qualitative methodology, emphasizing bibliographical and documentary research, fieldwork, and semi-structured interviews with the visited communities between 2019 and 2022. The thesis findings revealed that the agricultural frontier in the north of Tocantins was marked by disputes and conflicts that were shaped by processes described by Oliveira (1995). These processes included the monopolization of territory and the territorialization of monopolies, with livestock, soy production, and eucalyptus plantations being central elements driving the expansion of agribusiness into peasant and indigenous territories. These dynamics created conflict and fueled opposing forms of resistance. While violence and fear contributed to the disintegration of communities, they also strengthened the peasants' thirst for justice and their determination to fight for their land and conquered territories. The resistance of the peasantry in the North of Tocantins extended beyond organized socio-territorial movements. It manifested in their daily lives, their persistence in conflict zones, the preservation of their ways of life, the transmission of knowledge across generations, and their hopes for a better future.